Occupational radiation dose from gastrointestinal endoscopy procedures with special emphasis on eye lens doses in endoscopic retrograde cholangiopancreatography - Kaasalainen, Touko; Pekkarinen, Antti; Kylänpää, Leena; Rainio, Mia; Tenca, Andrea; Jokelainen, Kalle; Barner-Rasmussen, Nina; Puustinen, Lauri; Udd, Marianne; Lindström, Outi (Endoscopy International Open, 2023)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) procedures may result in remarkable radiation doses to patients and staff. The aim of this prospective study was to determine occupational exposures in gastrointestinal endoscopy procedures, with a special emphasis on eye lens dose in ERCP.Methods Altogether 604 fluoroscopy-guided procedures, of which 560 were ERCPs belonging to four American Society for Gastrointestinal Endoscopy procedural complexity levels, were performed using two fluoroscopy systems. Personal deep-dose equivalent Hp(10), shallow-dose equivalent Hp(0.07), and eye lens dose equivalent Hp(3) of eight interventionists and Hp(3) for two nurse dosimeters were measured. Thereafter, conversion coefficients from kerma-area product (KAP) for Hp(10), Hp(0.07), and Hp(3) were determined and dose equivalents per procedure to an operator and assisting staff were estimated. Further, mean conversion factors from Hp(10) and Hp(0.07) to Hp(3) were calculated.Results The median KAP in ERCP was 1.0 Gy·cm2, with mobile c-arm yielding higher doses than a floor-mounted device (P < 0.001). The median Hp(3) per ERCP was estimated to be 0.6 µSv (max. 12.5 µSv) and 0.4 µSv (max. 12.2 µSv) for operators and assisting staff, respectively. The median Hp(10) and Hp(0.07) per procedure ranged from 0.6 to 1.8 µSv. ERCP procedural complexity level (P ≤ 0.002) and interventionist (P < 0.001) affected dose equivalents.Conclusions Occupational dose limits are unlikely to be exceeded in gastrointestinal endoscopy practice when following radiation-hygienic working methods and focusing on dose optimization. The eye lens dose equivalent Hp(3) may be estimated with sufficient agreement from the Hp(10) and Hp(0.07).